Cervical Haematoma Secondary to Spontaneous Thyroid Haemorrhage - Almeida e Sousa, M (2022)
Spontaneous thyroid haemorrhage is rare, but it can be a potentially life-threatening condition in severe cases, due to acute upper airway compromise. We report the case of a 75-year-old patient on chronic anticoagulation therapy for atrial fibrillation, who presented with sudden painful neck bulging and dysphagia. Physical examination revealed a hard mass on the anterior left side of the neck. Preliminary laryngoscopy was normal. The diagnosis was made using ultrasonography and further characterization with computed tomography, showing haemorrhage of a thyroid nodule with capsular disruption and diffusion of the haematoma to the deep cervical spaces, causing important tracheal deviation and hypopharynx compression. The patient developed dyspnoea and ultimately required urgent hemithyroidectomy. This case also highlights the importance of having a high index of clinical suspicion and prompt imaging in patients with atypical presentations of a neck mass.